Benefit and performance impact analysis of using hydrogen fuel cell powered e-taxi system on A320 class airliner - Stockford, Jack andrew; Lawson, Craig P.; Liu, Z (Cambridge University Press, 2019)
This paper presents the work carried out to evaluate the benefits and performance impacts of introducing a hydrogen fuel cell powered electric taxiing system to a conventional short-haul aircraft. Tasks carried out in this research and reported in this paper include the initial system design, hydrogen tank initial sizing, calculation of the impact on fuel burn and emissions and the evaluation of the effects on Direct Operating Cost (DOC). The Airbus A320 has been selected as the datum aircraft for sizing the system, and the benefits analysis is particularly focused on the fleet composition and financial data of a Europe-based, low-cost, large-scale A320 family operator in 2016. The maximum power capacity of 400 kW has been sized based on the rolling friction coefficient of 0.02. Based on the operator’s 2016 financial, up to 1% fuel reduction can be achieved using the proposed system and the reduction in total maintenance cost is expected to be up to 7.3%. Additionally, up to 5.97% net profit improvement is estimated in comparison with the annual after-tax profit of the datum operator in 2016
Keywords: Electric taxiing system; Green taxiing system; Hydride aircraft; Poweredlanding gear; DOC reduction; More efficient aircraft